Creation of Third Space: A New Forged Identity in Jasmine and Seasons of Flight - Adhikari, Tara Prasad (Mindscape: A Journal of English & Cultural Studies, 2024)
This paper discusses the notion of the third space as the place of identity construction using some illustrative examples from Jasmine by Bharati Mukherjee and Seasons of Flight by Manjushree Thapa. Through the use of key ideas presented by Homi K. Bhabha, this paper reviews how the two protagonists, Jasmine and Prema, who are South Asian women migrants in the United States, encoded transnational displacement in their creation of hybrid identities. These characters change displacement to an act of self-reinvention by refusing the negative East/West and home/ exile binary relations. The study employs close reading of its text, exploring such characteristics as linguistic hybridity, symbolic reinvention and nonlinear narrative distributions, which reflect the fluid identities of the protagonists. The paper, inspired by the scholarship on diasporas, claims that in creative works by Mukherjee and Thapa, the third space is addressed as the space of the agency, which contests the nationalist patterns of belonging. Through cultural negotiation and evocation of memory, the novels bring about an innovative view of migrants, taking a radical stance in belonging to a globalized world through the process of building dynamic identities.